2016
DOI: 10.7150/thno.13515
|View full text |Cite
|
Sign up to set email alerts
|

Triple-Layered pH-Responsive Micelleplexes Loaded with siRNA and Cisplatin Prodrug for NF-Kappa B Targeted Treatment of Metastatic Breast Cancer

Abstract: The combination of chemotherapy and RNA interference is a promising approach for efficient cancer therapy. However, the success of such a strategy is hampered by the lack of suitable vectors to coordinate small interfering RNA (siRNA) and chemotherapeutic drug into one single platform. We herein report a novel triple-layered pH-responsive micelleplex loading siRNA and alkylated cisplatin prodrug for NF-Kappa B targeted treatment of metastatic breast cancer. The micelles were self-assembled from poly(ethylene g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 92 publications
(45 citation statements)
references
References 52 publications
1
43
0
1
Order By: Relevance
“…The 4T1 tumor model we used in this study is a highly aggressive TNBC tumor model, which is potent for distant lung metastasis . Figure A,B showed chemotherapy with Dox marginally inhibited tumor metastasis to the lung.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 4T1 tumor model we used in this study is a highly aggressive TNBC tumor model, which is potent for distant lung metastasis . Figure A,B showed chemotherapy with Dox marginally inhibited tumor metastasis to the lung.…”
Section: Resultsmentioning
confidence: 99%
“…Monotherapy or neoadjuvant chemotherapy using cytotoxic drugs is currently the standard‐of‐care for clinical treatment of advanced or metastatic TNBC . Unfortunately, systemic chemotherapy suffers from the severe side effects and the occurrence of acquired drug resistance due to nonspecific drug distribution to the normal tissues while insufficient drug delivery to the tumor in vivo . Recent study also revealed that systemic chemotherapy suppressed the immune activity by damaging the bone marrow and subsequently reduced the number of resident immune T cells, which impaired the therapeutic outcome of systemic chemotherapy …”
Section: Introductionmentioning
confidence: 99%
“…HOC is a Pt (IV) prodrug, which is inert in the blood circulation and is activated in the tumor cells by reducing HOC (IV) to OXA (II) with the endogenous glutathione (GSH). Such a prodrug strategy has been employed to improve the therapeutic outcomes of platinum drugs (e.g., OXA and cisplatin) while to suppress their side effect . The combination of DOX and HOC displayed a therapeutic combination index (CI) < 1.0 in 4T1 cells calculated according to a reported approach, indicating DOX potentially sensitized TNBC cells to HOC treatment (Table S1 and Figure S12, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…33 siRNA temelli tedavideki en büyük zorluklardan birisi sistemik taşınımla hedefe ulaşım olduğundan, son yıllarda siRNAların kimyasal modifikasyonu, biyoaktif moleküllere siRNA konjugasyonu ve taşınım formulasyonları ile ilgili çalışmalar yoğun şe-kilde devam etmektedir. [40][41][42][43][44][45] RNAi temelli tedavi yöntemlerinde immün cevap ve toksisite de bir başka problemdir. RNAi mekanizması, vücudu istenmeyen patojenlerden korumak için yer alan doğuştan bir immün cevap sistemidir.…”
Section: Rnai Mekani̇zmasi Ve Bi̇yogenezi̇unclassified